Leveraging technology for the recruitment of students and faculty - William Hoon; Christopher Hirschler (Academic Chairpersons Conference Proceedings, 2017)
This presentation will discuss some best practices in using the latest technology to assist in student and faculty recruitment in two distinct departments at two universities.
Keywords: recruiting; enrollment; management; social media